2022
DOI: 10.1039/d1cy02067f
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth of phosphorus-doped boron nitride on commercial alumina as a robust catalyst for direct dehydrogenation of ethylbenzene

Abstract: Direct dehydrogenation of ethylbenzene to styrene catalyzed by metal-free materials is one of the most challenging topics in the chemical industry currently. Here, PBN@Al2O3(N) synthesized by in-situ growth of phosphorus-doped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To further investigate the feasibility of PNO-800 in situ grown on a commercial carrier, we used conventional carriers such as SiO 2 , AlPO 4 , AlN and Al 2 O 3 . The catalytic performances of them as well as PBN-1.2/Al 2 O 3 , 28 which was previously reported, are shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 57%
“…To further investigate the feasibility of PNO-800 in situ grown on a commercial carrier, we used conventional carriers such as SiO 2 , AlPO 4 , AlN and Al 2 O 3 . The catalytic performances of them as well as PBN-1.2/Al 2 O 3 , 28 which was previously reported, are shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 57%
“…In our previous paper, we found that phosphorus‐doped h‐boron nitride (PBN) to be an efficient catalyst for DDH of ethylbenzene with N 2 P=O and N 3 P−OH as active sites [23] . In addition, considering the microporous structure of PBN which is disadvantageous to the mass transfer of ethylbenzene molecule, we fabricated the mesoporous PBN (m‐PBN) by thiourea‐assisted synthesis without changing active groups, and obtained significantly improved ethylbenzene conversion rate and stability [24,25] . As we know, in the process of hybrid‐doping or pore‐forming, the structural defects of the materials are always inevitable to be created.…”
Section: Introductionmentioning
confidence: 92%
“…[23] In addition, considering the microporous structure of PBN which is disadvantageous to the mass transfer of ethylbenzene molecule, we fabricated the mesoporous PBN (m-PBN) by thiourea-assisted synthesis without changing active groups, and obtained significantly improved ethylbenzene conversion rate and stability. [24,25] As we know, in the process of hybrid-doping or pore-forming, the structural defects of the materials are always inevitable to be created. However, as for the two materials of PBN and m-PBN, except the difference of pore structure, no obvious difference of the element content and the species constitution could be identified, which brought difficulty for the analysis and discussion of defects therein.…”
Section: Introductionmentioning
confidence: 99%
“…The mesoporous PBN/cordierite-supported catalyst was prepared using a method similar to that reported in our previous study . As shown in Figure , the catalyst preparation process mainly involved two steps: cordierite support processing and m-BNP precursor preparation.…”
Section: Experiments Detailsmentioning
confidence: 99%